Analysis of Microplastic Types and Abundance in Water, Sediments, and Lokan Clams (Geloina erosa) in the Coastal Waters of Sinaboi, Rokan Hilir - Nur’aini, Intan; Amin, Bintal; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2026)
The objective of this study is to identify the species and abundance in the water, sediment, and the lokan clam to determine differences in abundance among the water, sediment, and the lokan clam and to examine the relationship between abundance in the water and sediment and the abundance of the lokan clam. This study was conducted from October to December 2025 in the waters off Sinaboi Beach. The methods used in this study were a survey and purposive sampling, with samples collected directly at the study site. Sample analysis was performed at the Marine Chemistry Laboratory, Department of Marine Sciences, Faculty of Fisheries and Marine Sciences, Universitas Riau. Samples were collected from three types of test materials: water, sediment, and lokan clam from the waters off Sinaboi Beach. The results of the study showed that environmental parameters ranged from 7.38–8.20 for pH, 29–31°C for temperature, 24–29‰ for salinity, and 0.50–1.21 m/s for current velocity. Four types of microplastics were found in the water, sediment, and lokan clam: fibers, fragments, films, and foam. The average microplastic abundance in water was 0.45 particles/L. In sediment, it was 1.74 particles/g. The average microplastic abundance in lokan clam was 2.20 particles/g. Statistical analysis indicates a significant difference in microplastic abundance in water, sediment, and the lokan clam (p < 0.05). Microplastic abundance in sediment and the lokan clam shows a stronger correlation because clams are filter-feeding organisms that accumulate microplastics from sediment